باب النفاس من تتمة الإبانة عن أحكام فروع الديانة للإمام أبي سعد عبدالرحمن بن محمد المتولي المتوفى سنة 478 هـ : دراسة وتحقيق - تلمساني، أفنان بنت محمد بن عبدالمجيد (جامعة أم القرى, 2007)
استهدف هذا البحث تحقيق باب النفاس من كتاب تتمة الإبانة عن أحكام فروع الديانة لأبي سعد المتولي، وهو كتاب في فقه الإمام الشافعي، حوى كثير من المسائل المهمة خاصة في باب النفاس تتعلق بعبادة المرآة في هذه الفترة، وما يحل لها وما يحرم عليها، وقد تعرضت فيه بعد التعريف بالمؤلف والكتاب للمسائل التالية: 1- تعريف النفاس لغة وشرعا ٠ 2- حكم دم النفاس. 3- متى يثبت حكم النفاس على المرآة. 4- اكثر مدة النفاس. 5- أقل مدة النفاس. 6- انقطاع الدم في مدة النفاس ثم عوده فيها. 7- إذا زاد الدم على اكثر مدة النفاس. 8- حكم الدم النازل بين ولادة التوائم. This research aims to study a part of manuscript, which is ''lying-in'' unit, from the book for Abu Saad Al Motawally which called ''completing the appearance for judgment of the religion branches''. This book about Al Shafey jurisprudence which includes a lot of important problems about lying-in that relates with the woman worshipping in this period, and what is prohibiting and legitimating for her. After the definition with the author and the volume, I indicated to these points: 1. Lying in definition, linguistic and legislation. 2. The lying in blood judgment. 3. When the lying in judgment occurs on the woman. 4. The longest time for lying - in. 5. The shortest time for lying – in. 6. Absence the blood of lying – in and back. 7. If the blood increases more than lying – in period. 8. The descending blood judgment between the twins birth.
Keywords: الفقه الشافعي -- الفقه الاسلامي -- الأحكام الشرعية -- كتاب : تتمة الإبانة عن أحكام فروع الديانة -- النفاس -- المتولي ، عبدالرحمن بن محمد ، ت 479 هـ